PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Hot Kristian Maryanto; Emrinaldi Nur DP; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to test the Influence of Intellectual Capital and Good Corporate Governance on Firm Value With Financial Performance As an Intervening Variable In Manufacturing Company of Indonesia Stock Exchange Year 2011-2014. The target population in this study includes manufacturing companies listed in Indonesia Stock Exchange in 2011-2014. The samples were selected by purposive sampling method. The data used in this research is secondary data. Data collection method used is the method of documentation. The analytical method used in this research is path analysis. Based on the data collected and testing has been done on the problem by using the method of path analysis, it can be concluded: 1) Intellectual Capital has a significant effect on firm value. 2) Intellectual Capital has a significant effect on firm value through profitability. 3) Profitability has a significant effect on firm value. 4) Managerial Ownership has not a significant effect on firm value. 5) Managerial Ownership has not significant effect on firm value through profitability. 6) Proportion of Independent Commissioners has a significant effect on the value of the Company. 7) Proportion of Independent Commissioner has not a significant effect on firm value through profitability. 8) The Audit Committee has not a significant effect on firm value. 9) The Audit Committee has not a significant effect on firm value through profitability.Keywords: Intellectual, Capital, Governance, Values and Performance